Eggs as a Suitable Tool for Species Diagnosis of Causative Agents of Human Diphyllobothriosis (Cestoda). - Kateřina Leštinová; Miroslava Soldánová; Tomáš Scholz; Roman Kuchta (Public Library of Science (PLoS), 2016)
Tapeworms of the order Diphyllobothriidea are parasites of tetrapods and several species may infect man and cause neglected human disease called diphyllobothriosis. Identification of human-infecting diphyllobothriid cestodes is difficult because of their morphological uniformity, which concerns also their eggs in stool samples.In the present study, we analysed by far the largest dataset of more than 2,000 eggs of 8 species of diphyllobothriid cestodes that may infect humans, including the most frequent human parasites Diphyllobothrium latum, D. nihonkaiense and Adenocephalus pacificus (syn. Diphyllobothrium pacificum). Size (length, width and length/width ratio) and the surface of the egg shell from naturally and experimentally infected hosts were studied using light and scanning electron microscopy.A high degree of intraspecific and host-related size variability has been detected, but combination of morphometrical and ultrastructural data made it possible to distinguish all of the studied species, including otherwise quite similar eggs of the 3 most common species infecting man, i.e. D. latum, D. nihonkaiense and D. dendriticum. The surface of all marine species is covered by numerous deep pits with species-specific density, whereas the surface of freshwater species is smooth or with isolated shallow hollows or wrinkles.